1958
DOI: 10.1111/j.1365-2672.1958.tb00133.x
|View full text |Cite
|
Sign up to set email alerts
|

THE USE OF STORED SUSPENSIONS OF ESCHERICHIA COLI I IN THE EVALUATION OF BACTERICIDAL ACTION

Abstract: S U M M A R Y :Suspensions of Escherichia coli I, consisting of washed cells suspended in a phosphate buffer solution, maintained a higher viability and resistance to phenol than suspensions either of unwashed cells or of washed cells suspended in water. When stored for 5 weeks at room temperature, variations in their extinction times on exposure to aqueous phenol solutions were not significantly greater than variations with suspensions freshly prepared for each determination. Loss of resistance of a stored su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1959
1959
1976
1976

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Normally increased resistance of organisms to phenols is associated with increasing culture age (Cook & Wills, 1958). Cowen (1974) has shown that resistance ofPseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Normally increased resistance of organisms to phenols is associated with increasing culture age (Cook & Wills, 1958). Cowen (1974) has shown that resistance ofPseudomonas spp.…”
Section: Discussionmentioning
confidence: 99%